Quality Management of Al-Quran Education Using the Qiroati Method at TPQ Ar-Rahmah, Patean District, Kendal Regency: Manajemen Mutu Pendidikan Al-Quran dengan Metode Qiroati di TPQ Ar-Rahmah Kecamatan Patean Kabupaten Kendal - Khairunnisa, Sabrina; Mawardi, Imam (Prosiding University Research Colloquium, 2023)
Quality in Al-Quran education cannot be limited to general learning. However, in reality quality standards are seen in customer satisfaction which is not ignored. The aim of this research is regarding education quality management implemented at TPQ Ar-Rahmah which needs to be studied and carried out, considering that the quality of educational resources greatly influences the quality of students, in this case students and alumni. The design of this research is a field study. Using a qualitative research approach. The data collection method is by interviews with observed objects and direct observation. Guaranteeing the quality of learning and education services at TPQ has been carried out consistently in improving the quality of the ustad and ustadzah in providing close services to the students. Ustadzah and students at TPQ are advantages that must be maintained and developed.